2014
DOI: 10.1371/journal.pone.0105586
|View full text |Cite
|
Sign up to set email alerts
|

Key Role for Store-Operated Ca2+ Channels in Activating Gene Expression in Human Airway Bronchial Epithelial Cells

Abstract: Ca2+ entry into airway epithelia is important for activation of the NFAT family of transcription factors and expression of genes including epidermal growth factor that help orchestrate local inflammatory responses. However, the identity of epithelial Ca2+ channel that activates these transcriptional responses is unclear. In many other non-excitable cells, store-operated Ca2+ entry is a major route for Ca2+ influx and is mediated by STIM1 and Orai1 proteins. This study was performed to determine if store-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…The rates of Ca 2+ influx following Ca 2+ add-back reflect store-operated channel activity and are summarized in Figure 3E. These findings are consistent with recent reports indicating presence of CRAC channels in the bronchial cell lines 16HBE and CFBE410 − (21, 34). …”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The rates of Ca 2+ influx following Ca 2+ add-back reflect store-operated channel activity and are summarized in Figure 3E. These findings are consistent with recent reports indicating presence of CRAC channels in the bronchial cell lines 16HBE and CFBE410 − (21, 34). …”
Section: Resultssupporting
confidence: 89%
“…1). These findings confirm and broaden observations from past studies that have described STIM1 and Orai1 mediated SOCE in various airway epithelial cell-lines and corroborate the emerging viewpoint that CRAC channels are a well conserved mechanism for Ca 2+ influx in the lower airways (21, 34, 53). Our data however do not rule out a role for other CRAC channel isoforms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We and others have shown that CRAC channels are a major mechanism for eliciting Ca 2+ signals in AECs and are activated in response to PAR2 stimulation1516. The ensuing Ca 2+ elevation regulates the production of key inflammatory cytokines including IL-6, IL-8, and TSLP15.…”
mentioning
confidence: 98%